Effects of acute caffeine on muscle damage biomarkers and time to exhaustion after a single session of resistance exercises followed by exhaustive incremental test in long-distance runners - AbuMoh'd, M. F.; Shamrokh, N.; Bataineh, A.; Al-Horani, R. (Journal of Human Sport & Exercise, 2021)
The present study was designed to investigate the acute effect of caffeine on muscle damage biomarkers (creatine kinase, lactate dehydrogenase, creatine kinase MB, and myoglobin) measured before, immediately after, and 24 h after a single session of resistance exercises followed by exhaustive incremental test. In addition, the effect of caffeine intake on time to exhaustion during exhaustive incremental test was determined. Fifteen male long-distance runners (30.67 ± 3.40 yrs.) performed two consecutive trials (7 days apart). Athletes were assigned randomly either to ingest caffeine (6 mg/kg) 1 h prior to exercise or placebo using a double-blind crossover design. Each trial consisted of 5 resistance exercises followed by exhaustive incremental test. Blood samples were collected before, immediately, and 24 h after each trial. The independent t test of data showed no significant differences in biomarkers of muscle damage at all time points between trials (p > .05). Using paired sample t test, data revealed that caffeine increased the time to exhaustion (45.78 ± 2.42 min) during exhaustive incremental test compared to the placebo (43.83 ± 2.21 min) (p = .001). In conclusion, 6 mg/kg of caffeine 1 hour prior to resistance exercises followed by exhaustive incremental test had no effect on muscle damage biomarkers in long-distance runners probably due to mechanical stress precisely affected fast twitch fibres rather than slow twitch fibres. However, the increased time to exhaustion due to caffeine consume may attributed to dampened pain sensation.